The giant Mauritanian cold-water coral mound province: Oxygen control on coral mound formation. (1st April 2018) - Wienberg, Claudia; Titschack, Jürgen; Freiwald, André; Frank, Norbert; Lundälv, Tomas; Taviani, Marco; Beuck, Lydia; Schröder-Ritzrau, Andrea; Krengel, Thomas; Hebbeln, Dierk
Abstract: The largest coherent cold-water coral (CWC) mound province in the Atlantic Ocean exists along the Mauritanian margin, where up to 100 m high mounds extend over a distance of ∼400 km, arranged in two slope-parallel chains in 400–550 m water depth. Additionally, CWCs are present in the numerous submarine canyons with isolated coral mounds being developed on some canyon flanks. Seventy-seven Uranium-series coral ages were assessed to elucidate the timing of CWC colonisation and coral mound development along the Mauritanian margin for the last ∼120, 000 years. Our results show that CWCs were present on the mounds during the Last Interglacial, though in low numbers corresponding to coral mound aggradation rates of 16 cm kyr −1 . Most prolific periods for CWC growth are identified for the last glacial and deglaciation, resulting in enhanced mound aggradation (>1000 cm kyr −1 ), before mound formation stagnated along the entire margin with the onset of the Holocene. Until today, the Mauritanian mounds are in a dormant state with only scarce CWC growth. In the canyons, live CWCs are abundant since the Late Holocene at least. Thus, the canyons may serve as a refuge to CWCs potentially enabling the observed modest re-colonisation pulse on the mounds along the open slope. The timing and rate of the pre-Holocene coral mound aggradation, and the cessation of mound formation varied between the individual mounds, which was likely the consequence of vertical/lateral changes in water mass structure that placed the mounds near or out of oxygen-depleted waters, respectively. Highlights: Enhanced formation of Mauritanian coral mounds during the last glacial and deglacial. Coral mound aggradation reached rates of up to 16 m kyr −1 Mauritanian corals mounds are in a dormant state since the Early Holocene. Dissolved oxygen concentrations represent an important control on mound formation. Submarine canyons offer a refuge for cold-water corals and act as source for larvae supply.